Achieving global convergence of financial reporting standards : implications from the South Pacific region - Chand, Parmod; Patel, Christopher (Studies in managerial and financial accounting ;, 2011)
This research monograph examines whether International Financial Reporting Standards (IFRS) are interpreted and applied in a consistent manner within and across countries, and questions the implicit assumption that accounting convergence will automatically lead to comparability in financial reporting. Its review of the accounting judgment and decision making research published in the five top-tier accounting journals over the last forty years shows that there is a limited number of studies that have examined the importance of consistency in interpreting and applying a single set of accounting standards. Furthermore, the monographs and reviews on audit judgment and decision making research published over the years have strengthened this strand of research in auditing by providing insights and suggesting avenues for future research. However, limited comprehensive reviews have been published so far for the research undertaken in the domain of accounting judgment. This research monograph provides empirical evidence on the factors that act as constraints on achieving the objectives of convergence of financial reporting.